Confocal microscopy - Liu, Jian (Professor of electronic engineering and automation); Tan, J. (Jiubin) (IOP concise physics., 2016)
The confocal microscope is appropriate for imaging cells or the measurement of industrial artefacts. However, junior researchers and instrument users sometimes misuse imaging concepts and metrological characteristics, such as position resolution in industrial metrology and scale resolution in bio-imaging. And, metrological characteristics or influence factors in 3D measurement such as height assessment error caused by 3D coupling effect are so far not yet identified. In this book, the authors outline their practices by the working experiences on standardization and system design. This book assumes little previous knowledge of optics, but rich experience in engineering of industrial measurements, in particular with profile metrology or areal surface topography will be very helpful to understand the theoretical concerns and value of the technological advances. It should be useful for graduate students or researchers as extended reading material, as well as microscope users alongside their handbook.